Correlation between Asphaltene Stability in n-Heptane and Crude Oil Composition Revealed with Chemical Imaging - Anton A. Gabrienko; Velu Subramani; Oleg N. Martyanov; Sergei G. Kazarian (Adsorption Science & Technology)
Five crude oil samples with different physical properties have been studied with respect to asphaltene stability. The attenuated total reflection-Fourier transform infrared (ATR-FTIR) spectroscopic imaging approach of n-heptane-induced precipitation has been used to monitor crude oil behaviour under dilution with a flocculation agent. For each sample, the dynamics of asphaltene precipitation has been observed by applying this chemical imaging method. Based on these data, the stability of crude oil samples has been compared and the correlation between asphaltene stability and crude oil properties has been proposed.